TINJAUAN MAQASHID SYARIAH TERHADAP STATUS ANAK HASIL NIKAH LIKKA SORO’ DI MASYARAKAT ADAT MANDAR - Ririn Erisyam; Rusdaya Basri; Zainal said; Sudirman L (SAMAWA, 2025)
The Likka Soro’ marriage practice, which takes place among the Mandar indigenous community in West Sulawesi, is a form of customary marriage conducted without official state registration, yet it remains socially and religiously recognized. However, the existence of children born from such unions raises serious legal issues, particularly concerning lineage status, inheritance rights, and legal identity. This study aims to analyze the legal implications for children born from Likka Soro’ marriages and to examine the practice through the lens of maqashid syariah, particularly the principles of hifz al-nasl (protection of lineage) and hifz al-nafs (protection of life). The research employs a descriptive qualitative method, using a normative-theological approach and field study. The findings indicate that although Likka Soro’ is culturally accepted, the absence of formal registration results in a lack of legal protection for the children involved. From the perspective of maqashid syariah, such a practice contradicts the core objectives of Islamic law if it causes harm to children. Therefore, marriage registration should be promoted as a means of protecting children's rights within the framework of social justice, national law, and maqashid syariah. Keywords: Likka Soro’, Child Status, maqashid syariah.